2022
DOI: 10.1002/htj.22490
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of thermal radiation, Joule heating, and viscous dissipation effects on blood‐gold couple stress nanofluid flow driven by electroosmosis

Abstract: Gold nanoparticles associated with DNA, RNA, proteins, oligonucleotides, and peptides are useful in therapies and drug delivery. The present article mainatins that gold nanoparticles play a tremendous role in remedying cancer and fatal diseases. A mathematical model is proposed for the two-dimensional motion of the couple stress nanofluid consisting of gold nanoparticles under the application of peristaltic propulsion and electroosmosis mechanisms in an asymmetric microchannel. The effects of radiation with sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…34 Further investigations on heat transfer analysis and nanofluid can be found in the given Refs. [35][36][37][38][39][40] and several therein. The electro-osmotic flow (EOF) of various fluids is investigated in diverse microchannels, such as circular, elliptic, rectangular and slit microchannels.…”
Section: Mathematical Modeling and Simulation Of Electromagnetohydrod...mentioning
confidence: 97%
See 1 more Smart Citation
“…34 Further investigations on heat transfer analysis and nanofluid can be found in the given Refs. [35][36][37][38][39][40] and several therein. The electro-osmotic flow (EOF) of various fluids is investigated in diverse microchannels, such as circular, elliptic, rectangular and slit microchannels.…”
Section: Mathematical Modeling and Simulation Of Electromagnetohydrod...mentioning
confidence: 97%
“…It is possible to write the two-dimensional governing equations for the viscoelastic nanofluid with electroosmosis, radiation, Joule heating and magnetic field as follows 38 :…”
Section: Problem Descriptionmentioning
confidence: 99%
“…Hematocrit level and electric field variation affected the capillary filling process in microchannels, as stated by Chakraborty. 14 Recently, numerous researchers have studied the impact of electroosmosis modulated peristaltic flow in various geometries [15][16][17][18][19][20][21][22][23][24][25] and discussed the effects of the zeta potential, EDL thickness, and external electric field effects in both directions (in direction of fluid flow as well in the opposite direction of fluids flow) on the physiological transport phenomena and also reported that electric field could be applicable to control the physiological transport and maintain the electrolyte level of the physiological systems.…”
Section: Introductionmentioning
confidence: 99%
“…Ferdows et al 37 studied the impact of radiative flux on hydromagnetic flow from a curved stretching sheet, using MATLAB bvp4c quadrature, noting that the fluid velocity and temperature increase with curvature parameter, whereas higher magnetic parameter reduces velocity. Sridhar et al 38 have reported the combined effects of Joule heating and radiation on non-Newtonian fluid flow. Further analyses reporting on the dual effects of thermal radiation and Ohmic heating on stretching sheet flows include Sajid et al 39 (on ferrofluids), Shamshuddin et al 40,41 (on micropolar magnetic polymers and pseudoplastic magnetic polymers), and Prakash et al 42 (who used a tangent hyperbolic rheological model for biaxial electro-MHD stretching flow).…”
Section: Introductionmentioning
confidence: 99%